Genetic variation of an infraspecific chayote complex evaluated by isoenzimatic systems - Avendaño Arrazate, C. H.; Cadena Iñiguez, J.; Arevalo Galarza, M. L.; Cisneros Solano, V. M.; Aguirre Medina, J. F.; Moreno Pérez, E. del C.; Cortes Cruz, M.; Castillo Martínez, C. R.; Ramírez Vallejo, P. (Pesquisa Agropecuaria Brasileira, 2012)
<!–[if gte mso 9]> Normal 0 <![endif]–>The objective of this work was to estimate the degree of genetic variation in an infraspecific complex of Sechium using isoenzymatic systems. For this purpose, 23 loci were codified by 12 isoenzimatic systems and analyzed in starch gels, in 10 individuals from each of the 30 accesions of Sechium (27 cultivated and three wild relatives). The estimation of genetic variation was based on the average number of alleles per locus (NPAL), polymorphism percentage (PP), observed and expected heterozygosity (Ho and He), relative heterozygosity index (RHI) and Shannon´s index (IS). For NPAL and PP, the average for the 30 accesions was 2.03 and 59.8%, respectively. The analysis of Ho and He showed genetic variation in the infraspecific complex of Sechium, with 0.05 and 0.26 average values, respectively. The RHI showed a deficiency of heterozygote individuals (average of ‑0.75). The IS showed a great diversity in the 30 accesions (0.41). The populations with the greatest genetic variations were Negrito, Verde liso, Negro xalapa, Verde espinoso and Negro cónico; with intermediate variation were Castilla blanco, Caldero and Blanco pequeño; and with little variation were Castilla verde, Cambray and wild relatives.